Innovative Anti-inflammatory Approaches in Chronic Liver Disease and Fibrosis - Irene Sagay-Omonogor; Tolulope Bolarinwa; Opeoluwa Oluwanifemi Akomolafe (International Journal of Scientific Research in Chemistry, 2024)
Chronic liver disease and fibrosis are significant health burdens worldwide, driven by persistent inflammation that exacerbates liver damage and impairs function. Traditional anti-inflammatory treatments, including corticosteroids, NSAIDs, and antiviral therapies, have limitations such as side effects, limited efficacy, and the risk of resistance. This review explores innovative approaches to managing liver inflammation and fibrosis, focusing on biological therapies, gene therapy and RNA-based treatments, natural compounds and dietary interventions, and microbiome modulation. Biologics like monoclonal antibodies and cytokine inhibitors offer targeted reduction of inflammation, while gene editing technologies and RNA interference present precise molecular interventions. Natural compounds and dietary changes provide holistic benefits, and microbiome modulation reveals the potential of gut-liver interactions in treatment strategies. The future of chronic liver disease management lies in these novel therapies, promising enhanced efficacy, reduced side effects, and personalized treatment plans. Advancing these innovations from research to clinical practice is essential to improve patient outcomes and quality of life.
Keywords: Chronic liver disease; Liver fibrosis; Anti-inflammatory treatments; Gene therapy; Biological therapies